Employees' commitment to change: Personality traits and organizational culture - Marchalina, Leonis; Ahmad, Hartini (2017)
This study examines the influences of personality traits on the employees’ commitment to change that moderated by the organizational culture.The employee’s commitment to change is important for the large companies to sustain in the global economy. The Lewin’s Three Step Model underpin this study at which it believes on the variables that affect the departure from the status quo to the current state. The quantitative data was collected from the employees in the large companies that are listed in Bursa Saham Kuala Lumpur (BSKL) Malaysia.The research used a simple random sampling and a cross-sectional survey. The results showed there is a relationship between the personality traits and the employees’ commitment to change, moderated by the organizational culture This study meets the objectives that successfully discovered the connection among the identified variables that contributed to the organizational change and human resource literatures. The originality of the study is the establishment of the instruments and theoretical building on the personality traits, organizational change and employees’ Commitment to Change. Likewise, this study implies that both practitioners and leaders need to review how they could increase the employees’ commitment to change in the companies based on the various personalities.